2007
DOI: 10.1021/jp076271e
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Solubilities of Water and Hydrophobic Ionic Liquids

Abstract: The ionic nature of ionic liquids (ILs) results in a unique combination of intrinsic properties that produces increasing interest in the research of these fluids as environmentally friendly "neoteric" solvents. One of the main research fields is their exploitation as solvents for liquid-liquid extractions, but although ILs cannot vaporize leading to air pollution, they present non-negligible miscibility with water that may be the cause of some environmental aquatic risks. It is thus important to know the mutua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
409
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 406 publications
(453 citation statements)
references
References 57 publications
39
409
0
1
Order By: Relevance
“…Thus, the acidity of cyclic ILs derives mainly from the cation aromaticity and also from the number of atoms forming the ring. This higher acidity provided by aromatic and 5-member ring cations correlates well with their ability to be solvated by water by enhanced hydrogen-bonding, either in binary 58 or ternary aqueous systems. 59 On the other hand, for the non- , as experimentally observed.…”
Section: Experimental Kamlet-taft Solvatochromic Parametersmentioning
confidence: 75%
“…Thus, the acidity of cyclic ILs derives mainly from the cation aromaticity and also from the number of atoms forming the ring. This higher acidity provided by aromatic and 5-member ring cations correlates well with their ability to be solvated by water by enhanced hydrogen-bonding, either in binary 58 or ternary aqueous systems. 59 On the other hand, for the non- , as experimentally observed.…”
Section: Experimental Kamlet-taft Solvatochromic Parametersmentioning
confidence: 75%
“…Thus, ILs containing free halides or anions that could decompose to form free halides, such as BF 4 -or PF 6 -, were avoided 8,21 . The anions studied, bis(trifluoromethylsulfonyl)imide effects from water in the IL will be negligible [22][23] , but the effects of oxygen on degradation of the IL could have significant impact 24 . Further studies will be completed to compare the effects of an oxygen free environment with these results.…”
Section: Resultsmentioning
confidence: 99%
“…For the cation improvement study, the chloride anion was kept, while combined with the following cations: [ [33], and thus decreasing the energy of cavity formation to accommodate a vanillin molecule. However, the increase of the alkyl side chain length leads to a decrease on the strength of the coulombic and polar interactions, while increasing the dispersive interactions, between the IL ions [15,34]. Therefore, these two contributions will act in different directions leading to the observed maximum value on the partition coefficients at about [C 6 mim]Cl.…”
Section: Effect Of Il Ions In Vanillin Partitioningmentioning
confidence: 99%
“…Indeed, few years ago, Gutowski et al [12] showed that aqueous solutions of imidazolium-based ILs can form ATPS under the addition of appropriate inorganic salts, such as K 3 PO 4 . Since then, the equilibrium properties of systems comprising ILs, for the development of specific extraction and isolation procedures, have been inves- tigated at our laboratory [9,[13][14][15][16][17][18][19]. It was already shown that ATPS formed by K 3 PO 4 and ILs are extremely advantageous for the partition of several biomolecules yielding larger partition coefficients than those conventionally obtained with polymer-inorganic salts or polymer-polymer ATPS [6,10,13].…”
Section: Introductionmentioning
confidence: 99%